Flipbook-Based E-Module MABEJA Improves Cognitive Learning in Grade IV You said:: E-Modul Berbasis Flipbook MABEJA Meningkatkan Hasil Belajar Kognitif Kelas IV - Fatmawati , Fatmawati; Wulandari, Fitria (Indonesian Journal of Education Methods Development, 2024)
This study investigates the application of the MABEJA e-module (Magnets, A Magic Object), designed as a flipbook, on cognitive learning outcomes for grade IV elementary school students. Background: With the increasing integration of technology in education, effective digital learning tools are essential for enhancing student engagement and comprehension. Specific Background: Despite numerous educational technologies available, limited research focuses specifically on the efficacy of flipbook-based e-modules in elementary science education. Knowledge Gap: There is a need for empirical evidence on the impact of such interactive e-modules on student learning outcomes, particularly in cognitive assessments. Aims: This research aims to assess the effectiveness of the MABEJA e-module in improving cognitive learning outcomes among grade IV students at SD Negeri Banjarsari. Results: Utilizing a pre-experimental design with a One Group Pretest-Posttest framework, the study involved 21 students. Results showed a significant increase in average scores, from a pretest mean of 53.80 to a posttest mean of 68.57, indicating the e-module's effectiveness in enhancing cognitive learning outcomes. Novelty: The MABEJA e-module's unique flipbook format combines traditional learning with interactive elements. Implications: These findings suggest that the MABEJA e-module is a viable educational tool that can improve cognitive learning outcomes in elementary science, thereby contributing to the ongoing development of innovative teaching methods. Highlights: Effective Learning Tool: The MABEJA e-module significantly improved cognitive learning outcomes, with average scores rising from 53.80 to 68.57. Innovative Design: The flipbook format of the e-module enhances interactivity and engagement in elementary science education. Research Contribution: This study provides empirical evidence supporting the use of digital tools in improving student learning in elementary settings. Keywords: E-Modules, Cognitive Learning Outcomes, Flipbook, Elementary Education, Interactive Learning.